Aberrances of the Wound Healing Process: A Review - Montserrat Fernandez-Guarino; Jorge Naharro-Rodriguez; Stefano Bacci (Cosmetics)
Wound healing is a complex biological process that can lead to chronic wounds, keloids, and hypertrophic scars when disrupted. Chronic wounds result from a prolonged inflammatory phase and impaired re-epithelialization. Keloids are characterized by excessive collagen deposition beyond the original wound boundaries, driven by persistent inflammation and fibroblast hyperactivity. Hypertrophic scars, on the other hand, are confined to the wound edges and are caused by an imbalance in collagen synthesis and degradation, typically resolving over time. The therapeutic approach to wound healing impairment involves a range of strategies, including non-invasive (which focus on supporting the natural healing process), minimally invasive, and aggressive interventions (such as surgical approach, often reserved for severe or refractory cases). Emerging therapies, including stem cell treatments and botulinum toxin injections, offer new hope for improving outcomes in patients with wound healing impairments. This review highlights the distinct mechanisms underlying chronic wounds, keloids, and hypertrophic scars and discusses their respective therapeutic approaches, focusing on both established and emerging therapies. Understanding these mechanisms is crucial for optimizing treatment strategies and improving patient outcomes.